Map of Edmonton district, Alberta - Lynch, F. C. C. (Francis Christopher Chisholm), 1884-; Chalifour, J. E. (Joseph Epiphane), 1863-1953 (Department of the Interior Canada, 1930)
This is a map of Edmonton district in 1930 showing vacant Dominion lands, forest reserves, First Nations reserves, coal mines, oil and gas wells, water power plants, power lines, railroads, cities and towns. It includes information on homesteading. Scale 1:792,000, or 12.5 miles to 1 inch. Relief shown by spot heights. Includes information on homesteading. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Shows vacant Dominion lands, forest reserves, First Nations reserves, coal mines, oil and gas wells, water power plants, power lines, railroads, cities and towns.